DEFORMATION RETRACT OF A DIGITAL H-SPACE - Demi̇ralp, Sibel; Haçat, Gülnur (Journal of Universal Mathematics, 2019)
In this study we investigate some properties of digital H-spaces and digital H-groups. It is shown that a _-deformation retract of a digital H-group is itself a digital H-group. Also we prove that there is a functor from the homotopy category of the pointed digital images to the category of groups and homomorphisms.
Keywords: Matematik; Digital H-space; Digital H-group; K-react; K-deformation retract; Mathematical Sciences